(untitled) (Research, Society and Development, 2020)
The chronology of COVID-19 infections shows us that the first cases were reported in December 2019. A number of patients were admitted to hospitals with a respiratory disease of an unknown etiology in Wuhan, Hubei Province, China. The patients presented symptoms such as coughing, persistent fever, sore throat and pneumonia. The respiratory infection situation got worse rapidly and had a very fast spread. Soon after, it was reported that the causing agent of the disease had been confirmed as the novel Coronavirus (SARS-CoV-2), which belongs to the subfamily Orthocoronavirinae, of the family Coronaviridae in the order Nidovirales. On January 7, 2020, the disease was named as Coronavirus Disease 2019 (COVID-19) by the World Health Organization (WHO). Chloroquine (CQ), Hydroxychloroquine (HCQ), Remdesivir, Heparin, Convalescent Plasma, Corticosteroid, Anticoagulants, Lopinavir, Ritonavir, Ivermectin and Nitazoxanide are some of the drugs on the market that are being tested to combat COVID-19. The purpose of this literature review is to analyze studies regarding the healing potential of these drugs for COVID-19. Some researchers about the effectiveness of these medications, the success rate on viral diseases and its action potential by different mechanisms. Thus, given the researches analyzed in this study, it was evident for most authors that these drugs are promising treatments for COVID-19, while the vaccine is not manufactured and available.